Evaluating the success of phased-release reintroductions for captive-born cheetah (Acinonyx jubatus) in South Africa - Muller, Allison Anne (Stellenbosch : Stellenbosch University, 2022)
Thesis (MScConsEcol)--Stellenbosch University, 2022.